Sexual behaviour and social relationships among gelada baboons - Dunbar, RIM (Elsevier, 1978)
The effects of oestrus on the social behaviour of male and female gelada baboons (Theropithecus gelada) are quantitatively described. Oestrus was found to have little effect on the social behaviour of either the male or the female and does not disrupt to any significant extent the structure of social relationships among the members of the unit as a whole. The female is responsible for initiating most sexual interactions, but, other than this, does not show any marked increase in the amount of attention paid to the male. These results contrast with findings reported for other species of the baboon-macaque group, and the differences are discussed in relation to the contrasting social systems of these species.